An Algorithm to Find the Directed Minimum Spanning Trees - A, Navis Vigilia; J, Suresh Suseela (International Journal of Computer Sciences and Engineering, 2019)
New technologies and the deployment of mobile and nomadic services are driving the emergence of complex communications networks that have highly dynamic behaviour. This naturally engenders new route-discovery problems under changing conditions over these networks. Unfortunately, the temporal variations in the network topology are hard to be effectively captured in a classical graph model. In this paper, we use and extend a recently proposed graph theoretic model, which helps capture the evolving characteristic of such networks, in order to compute multicast trees with minimum overall transmission time for a class of wireless mobile dynamic networks. We first show that computing different types of strongly connected components in this model in NP-Complete, and then propose an algorithm to build all rooted directly minimum spanning trees in already identified strongly connected components.